Dinâmica do carbono- 13C de raízes e resíduos de parte aérea de culturas de verão em dois solos de várzea - Dossin, Mariana Ferneda (2016)
The use of isotopic techniques has been widely used in studies related to changes in the soil C. The chemical quality of crop residues and the type of management used are considered to be the main factors that control the dynamics of soil C. However, the stabilization of C derived from crop residues is also dependent on soil texture. Therefore, the objectives of these studies were: a) to evaluate the efficiency of repeat pulse labeling technique for the isotopic enrichment of leaves, stems and roots of rice, sorghum and soybeans plants with 13C under greenhouse conditions and b) to evaluate the dynamics of C during the decomposition of 13C enriched shoots and roots of rice, sorghum and soybean plants in two lowland soils with different texture. The studies were conducted in the greenhouse of the department of soils, Federal University of Santa Maria (UFSM), Brazil. In the first study, rice, sorghum and soybeans plants were exposed weekly to isotopic pulses with 33% 13CO2 atoms, for 1-1,5h in closed acrylic chambers till grain filling stage. Delta 13C enrichment, chemical composition and the recovery and distribution of 13C in plant parts and soil was determined. In the second study, enriched residues obtained in the first study were used to study the dynamics of C in two lowland soils The soils were Planossolo Hidromórfico Eutrófico gleissólico and Planossolo Hidromórfico Eutrófico arênico. The experimental design was completely randomized with three replications with 18 treatments, which were composed of a combination of 13C enriched shoots and roots with non-enriched shoots and roots (natural abundance). The soil was collected after 30, 90 and 180 days and the amounts of 13C remaining in residues and soil and the new C in soil was determined. The dry matter (DM) production and chemical composition of the residues was not affected by the 13C enrichment. The enrichment values were +377 for rice, + 466.5 for sorghum and + 453.7 for soybean. The isotopic enrichment of plants with 13C by repeated pulses was efficient for the homogeneous enrichment of rice, sorghum and soybean plants in greenhouse conditions. Regarding the dynamics of the soil C, the management of rice residues affected the decomposition and the addition of new C in the soil. The quality of the residues influenced the decomposition process. There was no difference in the decomposition of the roots of the three crop plants. The type of the soil did not affect the decomposition of shoot and root, residues of soybean, sorghum and rice plants. The amount of new C was influenced by the type of residues and soil. The roots contributed greater amounts of C in the soil in relation to the shoots.